SiSTL2 Is Required for Cell Cycle, Leaf Organ Development, Chloroplast Biogenesis, and Has Effects on C4 Photosynthesis in Setaria italica (L.) P. Beauv. - Zhang, Shuo; Tang, Sha; Tang, Chanjuan; Luo, Mingzhao; Jia, Guanqing; Zhi, Hui; Diao, Xianmin (Frontiers in Plant Science, 2018)
Deoxycytidine monophosphate deaminase (DCD) is a key enzyme in the de novo dTTP biosynthesis pathway. Previous studies have indicated that DCD plays key roles in the maintenance of the balance of dNTP pools, cell cycle progression, and plant development. However, few studies have elucidated the functions of the DCD gene in Panicoideae plants. Setaria has been proposed as an ideal model of Panicoideae grasses, especially for C4 photosynthesis research. Here, a Setaria italica stripe leaf mutant (sistl2) was isolated from EMS-induced lines of ‘Yugu1’, the wild-type parent. The sistl2 mutant exhibited semi-dwarf, striped leaves, abnormal chloroplast ultrastructure, and delayed cell cycle progression compared with Yugu1. High-throughput sequencing and map-based cloning identified the causal gene SiSTL2, which encodes a DCD protein. The occurrence of a single-base G to A substitution in the fifth intron introduced alternative splicing, which led to the early termination of translation. Further physiological and transcriptomic investigation indicated that SiSTL2 plays an essential role in the regulation of chloroplast biogenesis, cell cycle, and DNA replication, which suggested that the gene has conserved functions in both foxtail millet and rice. Remarkably, in contrast to DCD mutants in C3 rice, sistl2 showed a significant reduction in leaf cell size and affected C4 photosynthetic capacity in foxtail millet. qPCR showed that SiSTL2 had a similar expression pattern to typical C4 genes in response to a low CO2 environment. Moreover, the loss of function of SiSTL2 resulted in a reduction of leaf 13C content and the enrichment of DEGs in photosynthetic carbon fixation. Our research provides in-depth knowledge of the role of DCD in the C4 photosynthesis model S. italica and proposed new directions for further study of the function of DCD.